Converging Mechanisms of Epileptogenesis and Their Insight in Glioblastoma - Hills, Kate E.; Kostarelos, Kostas; Wykes, Robert C. (Frontiers in Molecular Neuroscience, 2022)
Glioblastoma (GBM) is the most common and advanced form of primary malignant tumour occurring in the adult central nervous system, and it is frequently associated with epilepsy, a debilitating comorbidity. Seizures are observed both pre- and post-surgical resection, indicating that several pathophysiological mechanisms are shared but also prompting questions about how the process of epileptogenesis evolves throughout GBM progression. Molecular mutations commonly seen in primary GBM, i.e. in PTEN and p53, and their associated downstream effects are known to influence seizure likelihood. Similarly, various intra-tumoural mechanisms, such as GBM-induced blood brain barrier breakdown and glioma-immune cell interactions within the tumour microenvironment are also cited as contributing to network hyperexcitability. Substantial alterations to peritumoural glutamate and chloride transporter expressions, as well as widespread dysregulation of GABAergic signaling are known to confer increased epileptogenicity and excitotoxicity. The abnormal characteristics of GBM alter neuronal network function to result in metabolically vulnerable and hyperexcitable peritumoural tissue, properties the tumour then exploits to favor its own growth even post-resection. It is evident that there is a complex, dynamic interplay between GBM and epilepsy that promotes the progression of both pathologies. This interaction is only more complicated by the concomitant presence of spreading depolarization (SD). The spontaneous, high frequency nature of GBM-associated epileptiform activity and SD-associated DC shifts require technologies capable of recording brain signals over a wide bandwidth, presenting major challenges for comprehensive electrophysiological investigations. This review will initially provide a detailed examination of the underlying mechanisms that promote network hyperexcitability in GBM. We will then discuss how investigation of these pathologies from a network level, and utilization of novel electrophysiological tools, will yield a more-effective, clinically-relevant understanding of GBM-related epileptogenesis. Further to this, we will evaluate the clinical relevance of current preclinical research and consider how future therapeutic advancements may impact the bidirectional relationship between GBM, SDs, and seizures.